The Antecedents of Patient Loyalty in Outpatient Department of An-Nisa Hospital Tangerang - Liowina Adlin Hokky; Innocentius Bernarto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to analyze: the positive effect of location and facilities on patient satisfaction, the positive effect of location and facilities on patient loyalty, and the positive effect of patient satisfaction on patient loyalty. Data collection was carried out using questionnaire. The target population of this research were outpatients with an age of at least 18 or above at An-Nisa Hospital Tangerang, who are willing to be respondents of this study, and have used outpatient services at An-Nisa Hospital Tangerang at least twice and within the period of November 2021. The number of samples were determined to be 300 samples. The sampling technique used was purposive sampling. Partial Least Square-Structural Equation modeling (PLS-SEM) is applied as a statistical analysis to this study. The results of data analysis showed that the location has a positive effect on patient satisfaction. In addition, facilities have a positive effect on patient satisfaction. Meanwhile, location does not have a positive effect on patient loyalty and facilities do not have a positive effect on patient loyalty. Finally, patient satisfaction has a positive effect on patient loyalty.